2016
DOI: 10.1007/jhep12(2016)054
|View full text |Cite
|
Sign up to set email alerts
|

Factorization for jet radius logarithms in jet mass spectra at the LHC

Abstract: To predict the jet mass spectrum at a hadron collider it is crucial to account for the resummation of logarithms between the transverse momentum of the jet and its invariant mass m J . For small jet areas there are additional large logarithms of the jet radius R, which affect the convergence of the perturbative series. We present an analytic framework for exclusive jet production at the LHC which gives a complete description of the jet mass spectrum including realistic jet algorithms and jet vetoes. It factori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 95 publications
(238 reference statements)
2
35
0
Order By: Relevance
“…1. We note that even though the factorized form of the cross section is derived for strictly R 1, it was found that the factorization is a very good approximation even for fat jets with a relatively large jet radius of R ∼ 0.7 and even above [60][61][62][63], as pointed out also in [24]. These observations imply that the power corrections of the form O(R 2 ) to the factorization theorem in Eq.…”
Section: First Step: Hard Collinear Factorizationmentioning
confidence: 50%
See 1 more Smart Citation
“…1. We note that even though the factorized form of the cross section is derived for strictly R 1, it was found that the factorization is a very good approximation even for fat jets with a relatively large jet radius of R ∼ 0.7 and even above [60][61][62][63], as pointed out also in [24]. These observations imply that the power corrections of the form O(R 2 ) to the factorization theorem in Eq.…”
Section: First Step: Hard Collinear Factorizationmentioning
confidence: 50%
“…The jet mass distribution has been addressed several times in the literature from the theoretical side, where the efforts have focused mostly on exclusive jet configurations where additional constraints are imposed on the final state particles, see for example [21][22][23][24] and references therein. While it is advantageous in some situations to consider exclusive final state jets, it is important to note that the inclusive jet cross section can be measured with the highest statistics since all jets in a given transverse momentum and rapidity interval are taken into account without any further restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper all the calculations are carried out in the small R limit. In this case, the small-angle soft mode along the jet direction can be singled out as an independent degree of freedom [32,34,61,62]. Such soft radiation is sensitive to the jet direction and the jet boundary and will be referred to as the coft mode in the following discussions, cf.…”
Section: Degrees Of Freedommentioning
confidence: 99%
“…where the jet mass m J has been adsorbed in the variable y but is bounded using the prescription of Ref. [17] by m J /p T < R/ p 2 ¼ 0.28 for the jet cone size R ¼ 0.4 given by…”
Section: A Inclusive Jets At the Lhcmentioning
confidence: 99%